Prefrontal reinstatement of contextual task demand is predicted by separable hippocampal patterns - Jiefeng Jiang (Nature Portfolio, 2020)
Spatial contexts are often predictive of the tasks to be performed in them (e.g., a kitchen predicts cooking). Here the authors show that the retrieval of task demand when encountering a spatial context depends on hippocampal-prefrontal interactions.